Diffusive thermal instability in premixed flame - Ahmad Faiz Mat Zin, 1985-, author; Mazlan Abdul Wahid, author; B. Rosnadiah, author; International Graduate Conference on Engineering and Science(2008: Johor Bahru) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL